Location, Localization, and Localizability Location-awareness Technology for Wireless Networks - Liu, Yunhao; Yang, Zheng; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Title: Location, Localization, Localizability Authors: Yunhao Liu Zheng Yang With the popularity of wireless networks, location-based service has become increasingly prevalent in our lives, and its applications range far and wide. For instance, E-911 in the United States, or corresponding E-112 in Europe, offers timely and accurate assistance to the emergency callers by locating them through mobile communications networks or GPS, and sensor network, a typical type of wireless ad-hoc networks, has shown great potential in environmental monitoring, industrial sensing, battlefield surveillance and more. Location, Localization, Localizability provides a comprehensive and in-depth look at location-awareness technology in today$1 (Bs popular wireless networks, but it does so in a way that is aware of the difficulty of organizing such information, given the obvious diversity of relevant networks. Therefore, from the perspective of application, the book focuses on wireless ad-hoc and sensor networks, in which the overwhelming majority of localization techniques are involved. It discusses a versatile array of techniques but also mentions other types of networks, such as WLAN and 3G mobile. In addition, this book is organized around three step-by-step themes: location, localization, and localizability. It first addresses location-based applications because those are closest to our daily lives. It then details localization approaches in-depth before covering other advanced topics such as localizability and location privacy. Aimed at technicians and practitioners in the industry of Real-Time Location Systems, this guidebook covers many localization algorithms in-depth while making their design and analysis accessible. Each chapter ends with a summary or comparative study, providing a bigger picture and facilitating understanding.s
Keywords: Engineering; Computers; Electrical engineering; Engineering; Signal, Image and Speech Processing; Communications Engineering, Networks; Information Systems and Communication Service; Electronic books